Efficacy of retinoid and salicylic acid in the treatment of different histological types of seborrheic keratosis - Cherneda, L. O.; Чернеда, Лілія Олексіївна (НУОЗ ім. П. Л. Шупика, 2022)
Seborrheic keratosis (SK) is a benign neoplasm of the skin, characterized by a high prevalence in the population, especially among middle-aged and elderly people. The lack of clinical guidelines for the treatment of this dermatosis contributes to the creation of recommended essences for the tactics of such patients.
Ефективність використання ретиноїду та саліцилової кислоти у лікуванні різних гістологічних типів себорейного кератозу
ORCID: 0000-0002-3057-8685